2010
DOI: 10.1097/brs.0b013e3181b9c986
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Lumbar Intervertebral Disc Calcification and Angiogenesis, and Their Correlation With Clinical, Surgical, and Magnetic Resonance Imaging Findings

Abstract: Disc nucleus pulposus microscopic calcification is a common event occurring in adult patients suffering from lumbar disc herniation. Mechanisms that link disc degeneration, angiogenesis, and calcification remain a focus for further researches that may be useful in future medical treatments before surgical treatment of lumbar disc herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…The ossification rate is known to correlate with the degeneration grade of intervertebral discs and the Modic type endplate (19). The underlying mechanisms responsible for the ossification of intervertebral discs are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ossification rate is known to correlate with the degeneration grade of intervertebral discs and the Modic type endplate (19). The underlying mechanisms responsible for the ossification of intervertebral discs are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These genes were among the top 20 differentially expressed genes between the experimental and the control groups. As regards the link between the intervertebral disc calcification and inflammation around the herniated discs (19), as well as the association between inflammation and ossification (46), we believe that the inflammatory factors coding DEGs may be specifically related to disc ossification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that expression of VEGF and nerve growth factor are significantly higher in degenerative disc with no herniation compared with herniated disc, and angiogenesis is related to the presence of nerve fiber ingrowth into degenerative IVD and the appearance of discogenic low back pain (Freemont et al, 1997(Freemont et al, , 2002. Additionally, VEGF has been suggested to promote ectopic calcification via increase in angiogenesis (Karamouzian et al, 2010). Thus, we can infer that increased VEGF expression may aggravate IVD degeneration through the progress of atherosclerosis or calcification leading to occlusion of endplate openings, and further exacerbate low back pain by inducing nociceptive nerve ingrowth into degenerated disc.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] In addition, as degeneration of the IVD and chronic lower back pain progresses, nerves and blood vessels are increasingly found in the inner part of the AF. 25 The growth of fibrocartilage-like tissue, bone, neural tissue, and blood vessels in IVDs during degeneration is suggestive of the presence of stem cells that either surround the IVD, 23,24 or are present within the IVD. Studies have shown that disc cells isolated from degenerated human disc expressed stem cell surface markers, including CD90, CD73, CD105, CD166, CD63, CD133, Notch1, Delta4, and Jaggerd1.…”
Section: Progenitor Cells In Intervertebral Discmentioning
confidence: 98%